Sustainable Development Prediction of Start-ups in Ukraine - SOKIL, Oleh; PODOLCHAK, Nazar; KNIAZ, Sviatoslav; SOKIL, Yana; KUCHER, Lesia (Journal of Environmental Management and Tourism, 2022)
The purpose of the article is to confirm the success of start-ups in Ukraine, which will be achieved through a trend analysis of the integral indicator of the success of start-ups in Ukraine using polynomial forecasting of the 4th degree. The research methodology is based on the analysis and collection of data on indicators of the effective existence of the macro and microenvironment in Ukraine, an index analysis of the most significant indicators characterizing the prospects and efficiency of start-ups, trend analysis. Empirical data allowed to formulate a hypothesis: that there is a theoretical and methodological ability of the integral indicator of the success of start-ups in Ukraine to ensure the relevant trends in their sustainable development. The specific features and stages of development of start-ups were analyzed in the article. The study notes recommendations for creating an effective start-up and its financing. The procedures for collecting, analyzing, and processing information made it possible to build a trend line and forecast an integrated indicator of sustainable development of start-up success in Ukraine.